Analysis of Brand Experience, Brand Love and; Brand Loyalty to Willingness to Pay Premium Price to Starbucks Indonesia Consumers in Jakarta - Syifa Ni’matun Nida; I Made Sukresna (PT. Publikasiku Academic Solution, 2023)
This study was conducted with the aim to analyze the factors that influence brand loyalty and willingness to pay premium price in Starbucks Indonesia consumers in Jakarta. The development of consumer relationships with brands has become a focus for every business. Through brand-related communication, the brand acts as a system that engages buyers and sellers. Not only limited to the relationship between consumers and brands, but also related to greater sales, price vulnerabilities, better loyalty, and higher margins. SEM (Structural Equation Modeling) analysis was used as a data analysis method in this study. The research model used in this study is second order. The use of SEM with PLS (Partial Least Square) approach was chosen because it can be used effectively with small sample sizes and complex models The sample of this study amounted to 114 Indonesian Starbuks consumers in Jakarta. The results showed that brand experience has a positive and significant effect on brand love, brand experience has a positive and significant effect on brand loyalty, brand love does not have a significant effect on willingness to pay premium price, love for brand has a positive and significant effect on brand loyalty, brand experience does not have a significant effect on brand loyalty.Willingness to pay premium price, as well as brand loyalty have a positive and significant effect on willingness to pay premium price.